1996
DOI: 10.1016/s0741-5214(96)70198-2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary recurrent carotid stenosis

Abstract: Patients who have secondary recurrent carotid stenoses can safely undergo a third carotid operation. Female habitual smokers with elevated lipid levels and an early restenosis appear to be at high risk of secondary recurrent carotid stenoses. When surgery is necessary, carotid resection with an interposition saphenous vein graft appears more durable than patch angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
3
14
1
1
Order By: Relevance
“…Second, the mismatch in properties between the PTFE patch and the host arterial wall produces high-stress concentrations at the patch-artery interface and causes the more compliant posterior native arterial wall to bulge out, resulting in high ES. The finding of highstress concentrations with CEAP is consistent with the clinical findings of Rosenthal et al(50), who demonstrated higher incidence of post-CEA restenosis at the level of the bulb in patients with CEAP.…”
supporting
confidence: 91%
“…Second, the mismatch in properties between the PTFE patch and the host arterial wall produces high-stress concentrations at the patch-artery interface and causes the more compliant posterior native arterial wall to bulge out, resulting in high ES. The finding of highstress concentrations with CEAP is consistent with the clinical findings of Rosenthal et al(50), who demonstrated higher incidence of post-CEA restenosis at the level of the bulb in patients with CEAP.…”
supporting
confidence: 91%
“…17,19,21,23,26 Most restenotic lesions (70%) are localized in the origin of the ICA. 3,32,48 In agreement with these findings, our results and pooled data from four reports that provided location data 17,21,23,43 counted a 30% incidence of major restenosis being located in the distal CCA.…”
Section: Discussionmentioning
confidence: 99%
“…There are only six reports of Ͼ100 procedures, 6,13,16,30,33,36 10 reports of 50 to 99 procedures, 7,14,15,17,19,23,24,27,34,35 and 14 reports of Ͻ49 procedures. 5,18,[20][21][22]25,26,28,29,31,32,37,38 The reported 30-day stroke and death rates range from 0% to 5.4% (Table I). The most important flaw of most of these reports is the lack of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These results compare favorably with those of other reports. 11,14,15 Fry et al 9 reported a combined perioperative stroke and death rate of 5% in a group of 20 subclavian-carotid bypasses. A similar perioperative stroke and death rate (4.3%-6.3%) was reported by Berguer et al 13,16 in 2 recent series of cervical bypasses.…”
Section: Commentmentioning
confidence: 99%